Verification in Results-Based Financing for Health : Summary of Findings and Recommendations from a Cross-Case Analysis - Vergeer, Petronella (World Bank, Washington, DC, 2017)
Despite the increasing popularity of Results Based Financing, there is little evidence or documentation of different verification strategies and how strategies relate to the verification results. Documentation of implementation processes including those pertaining to verification of outputs/results is lacking in World Bank-financed RBF projects in the health sector. The overall objective of this cross-case analysis is to expand knowledge about verification processes andpractices to address the design and implementation needs of RBF projects. This study adds toavailable knowledge by comparing the characteristics of verification strategies as well as available data on costs (using level of effort as a proxy), savings, and verification results to date in six countries: Afghanistan, Argentina, Burundi, Panama, Rwanda, and the UK. These case studies were purposively selected to explore a number of factors, including: how a variety of results are verified; how the verification strategy is being implemented at different levels in the health system; and the implications of having different types of actors (that is, third-party versus internal verifiers) involved in the verification process. In this cross-case analysis, the discussion of similarities and differences in verification methods across the six cases as well as the analysis of findings is guided by a conceptual framework developed for this study. This study presents seventeen key findings, and nine recommendations.